2011
DOI: 10.1007/s00204-011-0682-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA adducts and strand breaks in workers exposed to vapours and aerosols of bitumen: associations between exposure and effect

Abstract: To study the associations between exposure to vapours and aerosols of bitumen and genotoxic effects, a cross-sectional and cross-shift study was conducted in 320 exposed workers and 118 non-exposed construction workers. Ambient air measurements were carried out to assess external exposure to vapours and aerosols of bitumen. Hydroxylated metabolites of naphthalene, phenanthrene and pyrene were measured in urine, whereas (+)-anti-benzo[a]pyrene-7,8-diol-9,10-epoxide ((+)-anti-BPDE), 8-oxo-7,8-dihydro-2'-deoxygua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…Values for DNA strand breaks and 8-oxodGuo adduct from peripheral white blood cells were like those reported for controls in the Marczynski et al (2011) publication evaluating DNA damage in bitumen exposed workers. The pattern of response for nonsmokers indicated more DNA strand breaks preshift than postshift while more DNA adducts and greater percentage of apoptotic cells were seen postshift.…”
Section: Category 4 -Not Assignablesupporting
confidence: 72%
See 1 more Smart Citation
“…Values for DNA strand breaks and 8-oxodGuo adduct from peripheral white blood cells were like those reported for controls in the Marczynski et al (2011) publication evaluating DNA damage in bitumen exposed workers. The pattern of response for nonsmokers indicated more DNA strand breaks preshift than postshift while more DNA adducts and greater percentage of apoptotic cells were seen postshift.…”
Section: Category 4 -Not Assignablesupporting
confidence: 72%
“…This study indicated the potential influence of circadian rhythm on biomarkers. When considered with Marczynski et al (2011), a similar shift-work effect from general occupational exposure was observed, marginally enhanced by bitumen exposure but within the acceptable range of healthy individuals. Pesch et al (2011) and Lotz et al (2016) reported that PAC metabolites in urine of mastic asphalt workers could not be considered specific biomarkers of bitumen exposure in the workplace due to the weak correlation with airborne bitumen exposure levels.…”
Section: Category 4 -Not Assignablementioning
confidence: 56%
“…The first pathway includes formation of specific PAHs-DNA adducts (oxygen-independent reaction with DNA, type I reaction) (ref. 37 ), the second pathway includes induction of oxidative stress (oxygendependent mechanism, type II reaction) (ref. 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Asphalt workers showed an elevated level of DNA strand-breaks and oxidative DNA damage in some studies using comet assay (Toraason et al 2001;Cavallo et al 2006;Marczynski et al 2006Marczynski et al , 2011Lindberg Bacaksiz et al et al 2008). In the present study, we found that the workers exposed to asphalt fumes had significantly higher DNA damage than the controls.…”
Section: Discussionmentioning
confidence: 99%